2008
DOI: 10.1007/s11104-007-9528-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a rhizosphere β-galactosidase from Pisum sativum L.

Abstract: Plant enzyme activities in the rhizosphere potentially are a resource for improved plant nutrition, soil fertility, bioremediation, and disease resistance.Here we report that a border cell specific β-galactosidase is secreted into the acidic extracellular environment surrounding root tips of pea, as well as bean, alfalfa, barrel medic, sorghum, and maize. No enzyme activity was detected in radish and Arabidopsis, species that do not produce viable border cells. The secreted enzyme activity was inhibited by gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…An indication for the production of arabinogalactan proteins by pea roots has been made previously by several authors, and Ara and Gal have been reported as major sugar residues in root-secreted slime (Bacic et al, 1986;Moody et al, 1988;Knee et al, 2001;Xie et al, 2012). Furthermore, a pea border cell-specific b-galactosidase has been reported to be required for pea root growth, and although the endogenous substrate of this enzyme has not been determined, arabinogalactan proteins were proposed as candidates (Wen et al, 2008). Also, arabinogalactan protein epitopes were found to be highly expressed in Arabidopsis border-like cells (van Hengel and Roberts 2002;Vicré et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…An indication for the production of arabinogalactan proteins by pea roots has been made previously by several authors, and Ara and Gal have been reported as major sugar residues in root-secreted slime (Bacic et al, 1986;Moody et al, 1988;Knee et al, 2001;Xie et al, 2012). Furthermore, a pea border cell-specific b-galactosidase has been reported to be required for pea root growth, and although the endogenous substrate of this enzyme has not been determined, arabinogalactan proteins were proposed as candidates (Wen et al, 2008). Also, arabinogalactan protein epitopes were found to be highly expressed in Arabidopsis border-like cells (van Hengel and Roberts 2002;Vicré et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As such, the in situ analysis of GH activities responsible for the degradation of plant cell wall polysaccharides has received comparatively little attention, primarily due to a paucity of convenient assay methods (Vicente et al, 2007). Some notable exceptions include the use of commercially available X (5-bromo-4-chloro-3-indolyl glycoside) substrates for the detection of exoglycosidase activity (Monroe et al, 1999;Chantarangsee et al, 2007;Macquet et al, 2007;Wen et al, 2008). Likewise, transglycosylase activity has been visualized in higher plant and yeast cell walls using sulforhodamine-oligosaccharide acceptor substrates (Vissenberg et al, 2000;Bourquin et al, 2002;Nishikubo et al, 2007;Cabib et al, 2008).…”
mentioning
confidence: 99%
“…Plants with altered border cell numbers, border cell delivery, or border cell gene expression would be predicted to exhibit altered susceptibility to infection. Experiments therefore were designed to develop tools to test the impact of border cells on root infection using plants with altered expression of genes controlling border cell development (103)(104)(105)(109)(110)(111)(112)(113)(114). Altered border cell development was achieved in transgenic plants, but pleiotropic effects precluded their use in field studies.…”
Section: Plant Genes Controlling Border Cell Production and Propertiesmentioning
confidence: 99%
“…Curiously, transgenic roots with altered expression of a flavin-binding protein gene that is expressed only in border cells markedly altered root morphology as well as rate and direction of growth (103). A second border cell-specific gene was found to encode a galactosidase that functioned outside the cell at only the low pH characteristic of the root tip extracellular environment (105). This seemed to be a likely prospect for altered gene expression without pleiotropic effects on root development.…”
Section: Plant Genes Controlling Border Cell Production and Propertiesmentioning
confidence: 99%